Familism and youth: notes about working with young people in socio-education - Colombi, Bárbara Leite Pereira; Horst, Claudio Henrique Miranda (Argumentum, 2021)
The article reflects on the contradictory relationship between the state socio-educational policy, aimed at young people between 18 and 21 years, and the family. It is based on a systematization of professional practice and a comparative literature review. The limits of the Brazilian State and the family strategy aimed at the public stand out. Finally, it concludes that the intended audience, young people between the ages of eighteen and twenty-one, without a family, and who are complying with socio-educational measures, become funneled into situations in which they become disposable, sometimes due to the lack of a family bonds and sometimes due to ineffectiveness of state action.